43rd Winter School on Vibroacoustical Hazards Suppressions - Roman BUKOWSKI (Archives of Acoustics)
Traditionally, the 43rd Winter School on Vibroacoustical Hazards Suppressions national conference was organized by Upper Silesian Division of the Polish Acoustical Society (main organizers) and by The Committee on Acoustics of The Polish Academy of Sciences (co-organizer). The Conference, as in previous years, was held in Szczyrk.